Penatalaksanaan Fisioterapi Pada Kasus Trigger Finger Dextra Dengan Modalitas InfraRed, Ultrasound Dan Transverse Friction - Sahnaz Praramadani; Ika Rahman (LPPM STIKES Siti Hajar dan Insight Power, 2021)
Trigger Finger is a disease that occurs in the fingers, a condition locked finger joint when they are moved from a flexion position to an extension position. Trigger finger is due to local inflammation or swelling of the flexor tendon sheath that prevents the sheath from sliding normally. To find out the management of physiotherapy in reducing pain, increasing muscle strength and increasing the range of motion of the joints in patients with Trigger Finger with Infrared, ultrasound, and transverse friction modalities. After doing therapy 6 times, the results were a decrease in silent pain T1: 5 T6: 0, tenderness T1: 8 to T6: 2 and motion pain T1: 9 to T6: 2. Increased flexion muscle strength from T1: 3 to T6: 5 and extension T1: 3 to T6: 5. Increased range of active joint motion on flexion movement Proximal Interphalang dextra T1: 1110 to T6: 1130. Infrared, Ultrasound and transverse friction can help reduce pain, increase muscle strength and increase joint range of motion in the case of Trigger Finger.Keywords: Trigger finger, Infrared, Ultrasound, Transverse Fiction.